The Assessment of CO2 Backproduction as a Technique for Potential Leakage Remediation at the Ketzin Pilot Site in Germany. (July 2017) - Govindan, Rajesh; Si, Guangyao; Korre, Anna; Durucan, Sevket; Wiese, Bernd; Schmidt-Hattenberger, Cornelia; Liebscher, Axel
Abstract: As part of the license application, CO2 storage projects must develop a corrective measures plan, which describes the steps that can be taken when the plume in the subsurface behaves in an unpredicted and undesired manner. One possible technique in the toolbox of corrective measures is CO2 backproduction, which has the potential for both pressure management and plume steering in the reservoir. The feasibility of this technique has recently been tested during a field experiment at the Ketzin pilot site in Germany. In this paper, the authors describe an assessment of backproduction using coupled flow and geomechanical modelling. In line with the field observations, the simulation results obtained also suggest that it is a stable and promising remediation technique.